THE Analisis Tingkat Pengetahuan dengan Kepatuhan berobat Pasien Tuberkulosis di Rumah Sakit Umum Daerah Provinsi NTB: Analisis Tingkat Pengetahuan dengan Kepatuhan berobat Pasien Tuberkulosis di Rumah Sakit Umum Daerah Provinsi NTB - Jupriadi, Lalu; Pratiwi, Dita Retno; Firmansyah, Dodiy; Pujiastutik, Tri Dian (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2023)
Tuberculosis (TB) is still a problem that must be addressed in the community, treatment programs and management guidelines have also been undertaken by the government to handle this case according to national standards. This is because there is still a high rate of non-adherence to treatment in TB patients. One of the causes of the high incidence of tuberculosis is due to knowledge, in this case the level of one's knowledge has a relationship with adherence to taking anti-tuberculosis medication. The number of people with pulmonary tuberculosis continues to increase from 2020 to 2022. This is because the high rate of non-adherence to treatment in tuberculosis (TB) patients is still high. Tuberculosis is caused by Mycobacterium tuberculosis which infects latently or progressively attacks the lungs. Purpose: This study was conducted to analyze the relationship between the level of knowledge of tuberculosis patients about tuberculosis and adherence to treatment of outpatient pulmonary tuberculosis patients at the Regional General Hospital of West Nusa Tenggara Province in 2022. Methods: This study was conducted using a Cross Sectional Study design. Population: in this study, the population used was patients with outpatient pulmonary tuberculosis at the Regional General Hospital of West Nusa Tenggara Province with a total sample of 57 respondents. Measuring tools used in the form of questionnaires and form TB 01. Data analysis using univariate and bivariate analysis with the Chi-Square test. Result: this study shows that there is a relationship between knowledge and medication adherence (p=0.025). It can be concluded that there is a significant relationship between knowledge and adherence to treatment in outpatient pulmonary tuberculosis patients at the Regional General Hospital of West Nusa Tenggara Province in 2022.